Konseling Multibudaya Berbasis Konseling KIPAS (Kajian Reflektif atas Pengalaman Konselor di Lembaga Pendidikan Tinggi) - Gudnanto Gudnanto; Iwan kuswandi (STKIP PGRI SUMENEP, 2020)
KIPAS Counseling is a summary of Progressive and Adaptively Intensive Counseling in terms of Structure. KIPAS is encouraged as a fresh breeze that is expected to calm all of the parties within BK's scientific disciplines down; from counselors, counselees, teachers, principals, and other elements that support it. KIPAS are present to eliminate the negative judgments that have been inherent in the mind of the counselees. The form of counseling services encouraged by cultural encounters and individual uniqueness proposes a more conducive and representative space, as a formula so that the prescription stipulated is correct. Multicultural Counseling is present as an answer to the uniqueness of each individual in realizing themselves as an autonomous person based on physical sensation and psychological states counselees, respect for the attitude of counselees, religious values, and cultural values of counselees, the flexible and positive attitude, also psychical satisfaction of the subject.